Associations of Common Variants at APLN and Hypertension in Chinese Subjects with and without Diabetes. (17th December 2012) - Zhang, Rong; Lu, Jingyi; Hu, Cheng; Wang, Congrong; Yu, Weihui; Jiang, Feng; Tang, Shanshan; Bao, Yuqian; Xiang, Kunsan; Jia, Weiping
Abstract : Background . Apelin, the endogenous ligand for the APJ receptor, has a potent hypotensive effect via a nitric oxide-dependent mechanism in vivo. The aim of the study was to investigate the association between the common variants of apelin gene ( APLN ) and hypertension, which was reported recently in a Chinese Han population with and without diabetes. Methods . Three single nucleotide polymorphisms (SNPs) on APLN were genotyped in 3156 diabetic patients and 3736 nondiabetic individuals. For non-diabetic subjects, 1779 were enrolled in stage 1 and 1757 were recruited for validation. A meta-analysis combining the two stages was carried out to obtain the overall effect. Results . In diabetic patients, no significant associations of the three SNPs with hypertension were observed. In contrast, we found that rs2235306 was associated with hypertension in non-diabetic males after adjusting for covariates (OR = 1.19, P = 0.039 ) while rs2235307 and rs3115759 displayed no evidence of association in both genders. One haplotype, C-C-A, also showed an association with hypertension (OR = 1.47, P = 0.032 ) only in men. However, analysis in stage 2 and meta-analysis did not support these findings. Conclusions . We conclude that common variants on APLN are not associated with the prevalence of hypertension in the Chinese.